Remaxol Hepatoprotective Therapy of Patients with Tuberculosis and HIV Infection in Day Unit of Tuberculosis Dispensary - E. V. Shevyreva; A. K. Ivanov; D. S. Sukhanov; A. A. Murzina (Антибиотики и Химиотерапия)
To improve the treatment of hepatotoxic responses to antituberculosis polychemotherapy, the impact of remaxol on the biochemical indices and parameters of the antioxidant system in patients with tuberculosis and HIV infection was estimated. The use of remaxol having cytoprotective, anticholestatic, antihypoxitic and antioxidant effects in the treatment of patients with tuberculosis and HIV infection and liver drug damage due to tuberculosis polychemotherapy significantly improved the biochemical indices and lowered the level of the cytolytic and cholestatic syndromes. Remaxol increased the antioxidant system potential and had an antihypoxitic effect.